2010
DOI: 10.1016/j.jaging.2008.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Narrative analysis in aging studies: A typology for consideration

Abstract: This article seeks to expand our understanding on narrative and the analysis of stories researchers invite and collect in the domain of aging studies. To do so, we first offer an understanding of what narrative inquiry can be by laying out a theoretical basis for this kind of research, and making a case for the relevance of narrative as an alternative methodology. Painting with broad strokes, narrative analysis as a method is then considered before a typology of different ways in which stories can be analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(137 citation statements)
references
References 53 publications
1
135
0
1
Order By: Relevance
“…The aim was to explore crisis by way of these interview narratives, interpreting it 'abductively' through the four conceptual levels described above, and then to derive a provisional holistic model inductively based on generalities across the cases studied. There is precedent for studying the challenges of ageing using narrative interview-based data (Phoenix, Smith & Sparkes, 2010;Torges, Stewart & Duncan, 2009;Walaskay, Whitbourne & Nehrke, 1983), and indeed…”
Section: Research Aim and Questionsmentioning
confidence: 99%
“…The aim was to explore crisis by way of these interview narratives, interpreting it 'abductively' through the four conceptual levels described above, and then to derive a provisional holistic model inductively based on generalities across the cases studied. There is precedent for studying the challenges of ageing using narrative interview-based data (Phoenix, Smith & Sparkes, 2010;Torges, Stewart & Duncan, 2009;Walaskay, Whitbourne & Nehrke, 1983), and indeed…”
Section: Research Aim and Questionsmentioning
confidence: 99%
“…Atkinson (2007) suggests that the life story interview can be seen as a natural bridge between the disciplines using narrative inquiry methodologies; between the 11 telling and living of a narrative; and between the whole and the parts of the life being narrated. Accordingly, the transcripts were subjected to various forms of narrative analysis described by Phoenix, Smith and Sparkes (2010) and Riessman (2008).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, Day, Bond, and Smith (2013) suggested that a collective 8 case can be used to demonstrate the complexities that may exist in a single context, 9 such as the rehabilitation or exercise environment. 10 The context of the collective case used in this study was an exercise 11 programme developed to improve physical function, specifically, balance and stability, 12 in order to prevent falls in older adults. This programme was based in a rural location 13 and lasted for 32 weeks.…”
Section: Participants and Contextmentioning
confidence: 99%